Pembelajaran Sastra Berbasis Karya Sastra yang Bersumber dari Majalah Suara 'Aisyiyah - Firdaus, Asep; Suparman, Fauziah (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
This research aims to determine the use of teaching materials for literary works sourced from Suara 'Aisyiyah magazine. The method used in this research is a qualitative research method with descriptive analysis techniques. This research describes the suitability of implementing poetry sourced from the magazine Suara ‘Aisyiyah to be used as teaching material in literature learning at Muhammadiyah High School, Sukabumi City. The results of the analysis show that the poems taken and used in literature learning at the Muhammadiyah High School in Sukabumi City, namely the poems